Clinical Characteristics of Patients with Diabetic Nephropathy on Maintenance Hemodialysis: A Multicenter Cross-sectional Survey in Anhui Province, Eastern China - Chen, Hu (Chin Med J (Engl), 2016)
BACKGROUND: The incidence of diabetic nephropathy (DN) increases year by year. However, clinical characteristics of DN patients on maintenance hemodialysis (MHD) were rarely reported in China. The purpose of this study was to examine the clinical characteristics of the DN patients on MHD in Anhui Province, Eastern China. METHODS: The clinical data of MHD patients in the hemodialysis centers of 26 hospitals in Anhui Province from January 1, 2014, to March 31, 2014, were examined. The differences between DN patients and non-DN patients were compared regarding vascular access, nutritional status, mineral and bone disorder, and other indexes. RESULTS: Among the selected 2768 adult MHD patients, 427 had DN. The incidence of hypertension, coronary heart disease, and cerebral thrombus in DN patients was 94.1%, 21.5%, and 15.0%, respectively, which were higher than those in non-DN patients (P < 0.001). Category of vascular access for hemodialysis in DN patients was arteriovenous fistula (AVF) (87.4% [373/427]) and tunneled cuffed catheter (TCC) (11.2% [48/427]). The percentage of AVF was significantly lower than that of non-DN patients (P < 0.001), and percentage of TCC was significantly higher than that of non-DN patients (P < 0.001). Hemoglobin achievement rate in DN patients was 32.0%. The incidence of hypoalbuminemia was 24.7%, significantly higher than that in non-DN patients (P < 0.001). The achievement rate of the target range in mineral values was 55.9% in corrected serum calcium level, 30.1% in serum phosphorus level, and 49.3% in intact parathyroid hormone (iPTH) level in DN patients. Compared with non-DN patients, the achievement rate of serum phosphorus was significantly higher in DN patients. CONCLUSIONS: DN patients on MHD in Anhui province exhibited different clinical characteristics compared to non-DN hemodialysis patients. They presented higher percentage in TCC use and cardiovascular complication, lower serum albumin and iPTH levels than those in non-DN patients.